1994
DOI: 10.1111/j.1365-2141.1994.tb04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive induction/consolidation therapy without maintenance in adult acute lymphoblastic leukaemia: a pilot assessment

Abstract: Maintenance chemotherapy for up to 3 years is traditionally given to patients with acute lymphoblastic leukaemia (ALL) achieving complete remission. We questioned the value of such maintenance therapy in adult patients treated with intensive induction/consolidation. In a phase II study (SAKK 33/86) 63 patients between 17 and 72 years of age (median 27 years) with newly diagnosed ALL were treated with three intensive cycles of marrow-ablative chemotherapy. All subtypes were included. No maintenance phase was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Similarly, treatment protocols for ALL include a period of high-intensity induction, followed by a milder dose consolidation, followed by 2–3 years of lower-dose, higher-frequency maintenance therapy [88]. This strategy gives 90–95% survival rates, and any attempts to omit the maintenance therapy yield inferior results [23, 73, 93]. Choi et al [18] reported encouraging results for a small group of children with tumors of central nervous system treated with upfront high-dose chemotherapy, followed by metronomic maintenance therapy.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…Similarly, treatment protocols for ALL include a period of high-intensity induction, followed by a milder dose consolidation, followed by 2–3 years of lower-dose, higher-frequency maintenance therapy [88]. This strategy gives 90–95% survival rates, and any attempts to omit the maintenance therapy yield inferior results [23, 73, 93]. Choi et al [18] reported encouraging results for a small group of children with tumors of central nervous system treated with upfront high-dose chemotherapy, followed by metronomic maintenance therapy.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…Maintenance therapy, usually consisting of 6‐mercaptopurine and methotrexate, and in some studies augmented by pulses of vincristine and prednisone, is generally administered for a total treatment duration of 2–3 years. Earlier attempts to omit maintenance therapy after intensive induction and consolidation treatment clearly led to inferior results unless patients were transplanted (43, 70, 71). On the other hand, no large or randomized trial has demonstrated a clear advantage for patients treated with intensive maintenance therapy compared to those with conventional maintenance.…”
Section: Treatment Of Adult Allmentioning
confidence: 99%
“…Patients were referred between 1995 and 2009 from the university hospitals of Basel, Zurich, Bern, Lausanne and cantonal/regional hospitals of St-Gallen, Aarau, Mendrisio, Bellinzona, and Genolier Clinic. Two patients were enrolled in the SAKK ALL 33-86/90 [6] and GRAALL 2005 clinical trials, respectively. Ethical approval for this project was obtained in accordance with the guidelines of the local Ethical Review Board.…”
mentioning
confidence: 99%
“…Approaches used and cutoff levels were reported in detail previously [4,7]. Table 1 Clones involving chromosomes 4, 6, 10, and 17 at presentation and/or during the course of disease in ten patients with high hyperdiploid acute lymphoblastic leukemia, expressed as percentages (13) 29 (13) 24 (15) 13 (8) 18 (15) 44 (34) 6 (3) 8 (5) 19 (16) 40 (25) 7 (7) 3 (3) 20 (13) 56 (43) 12 (9) 2 (1) 8 (5) 7 (6) Values in parentheses are numbers of very small abnormal clones (<1%). Clones already present in the previous analysis (<1%) are italicized.…”
mentioning
confidence: 99%